Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VIII SMPN 43 Padang - Fazqurni, Nisa Amelia (Jurnal Edukasi dan Penelitian Matematika, 2024)
Proficiency in mathematical problem solving is essential for students to navigate through the various stages and arrive at the desired solution in mathematics. Nevertheless, during the 2023/2024 academic year, pupils in class VIII at SMP Negeri 43 Padang continue to exhibit little proficiency in solving mathematical issues. The test result data indicates this. We are intrigued by the prospect of implementing Problem Based Learning (PBL) as an instructional framework. In order to improve students' problem solving skills in mathematics, a study was conducted comparing the PBL model with conventional direct learning. This study used the Nonequivalent Posttest-Only Control Group design. Sampling was done randomly in this study. Students of class VIII.2 became the control group, while students of class VIII.1 became the experimental group. The absence of a P-value greater than the significance level α = 0.05 led to the rejection of the null hypothesis (H0).Keywords – Mathematical problem solving ability, PBL, direct learning